Information Management and Critical Thinking–Strategic Decision-Making Competencies of First-Line Nurse Managers and the Achievement of Minimum Service Standards for Older Adults: The Mediating Role of Job Satisfaction: Job Satisfaction - Rakhmawati, Rani; Ahsan, Ahsan; Hayati, Yati Sri (Jurnal Keperawatan, 2026)
Introduction: The increasing number of older adults poses growing challenges for primary healthcare services, particularly in achieving the Minimum Service Standards (MSS) for elderly health. In community health centers (Puskesmas), first-line nurse managers play a strategic role in planning, implementing, and monitoring health programs for the elderly. However, achievement of MSS varies across facilities, suggesting that managerial competencies and work-related factors may influence service outcomes.Objective: This study aimed to examine the direct and indirect relationships between first-line nurse managers’ managerial competencies—specifically information management, critical thinking, strategic decision-making, and the achievement of Minimum Service Standards for elderly health, with job satisfaction as a mediating variable.Methods: An analytical quantitative cross-sectional study was conducted among 126 first-line nurse managers from 17 community health centers in Malang City and Malang Regency, Indonesia. Data were collected using the Primary Care Manager’s Managerial Competence Scale (15 items) and the short version of the Minnesota Satisfaction Questionnaire (16 items). Data were analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM).Results: Critical thinking–strategic decision-making competence showed no significant direct association with MSS achievement (β = −0.012; T = 0.740; p = 0.460), nor did information management competence (β = −0.016; T = 0.734; p = 0.463). However, mediation analysis revealed significant indirect associations through job satisfaction. Critical thinking–strategic decision-making competence demonstrated a positive indirect association with MSS achievement (β = 0.028; p = 0.021), while information management competence also showed a significant indirect association (β = 0.037; p = 0.024).Conclusion: Managerial competencies of first-line nurse managers were not directly associated with the achievement of Minimum Service Standards for elderly health. However, these competencies showed significant indirect associations with MSS achievement through job satisfaction, highlighting the importance of fostering supportive work environments to enhance elderly health service performance in primary care settings.